2020
DOI: 10.21203/rs.2.15686/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research transparency promotion by surgical journals publishing randomised controlled trials: a survey

Abstract: Objective: To describe surgical journals’ position statements on data-sharing policies (primary objective) and to describe key features of their research transparency promotion.Methods: Only “SURGICAL” journals with an impact factor higher than 2 (Web of Science) were eligible for the study. They were included, if there were explicit instructions for clinical trial publication in the official instructions for authors, (OIA) and or if they had published randomized controlled trial (RCT) between 1st January 2016… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Studies whose primary topic related to noninvasive procedures (e.g., casting, shockwave lithotripsy, bracing, molding), postoperative therapies (e.g., tranexamic acid for postoperative bleeding, opioids and nerve blocks for postoperative pain, radiation as neoadjuvant therapy post tumor resection), fetal surgery, anesthetics, intensive care, dentistry, nursing or meta-research were not included. 3 The study was published in full in 2021. Study protocols and studies written as replies, letters to the editor or secondary analyses were not included because their risk of bias and reporting quality could not be adequately assessed.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies whose primary topic related to noninvasive procedures (e.g., casting, shockwave lithotripsy, bracing, molding), postoperative therapies (e.g., tranexamic acid for postoperative bleeding, opioids and nerve blocks for postoperative pain, radiation as neoadjuvant therapy post tumor resection), fetal surgery, anesthetics, intensive care, dentistry, nursing or meta-research were not included. 3 The study was published in full in 2021. Study protocols and studies written as replies, letters to the editor or secondary analyses were not included because their risk of bias and reporting quality could not be adequately assessed.…”
Section: Studiesmentioning
confidence: 99%
“…Similarly, a systematic review of studies in pediatric surgery published in 1998 and 2013 found that only 1.8% and 1.9%, respectively, were RCTs [2]. These figures are even poorer than those for adult surgery: a review of 87 surgical journals by Lombard et al (2020) found that only 18% of surgical journals had published an RCT between 2016 and 2018 [3]. This is a long-standing trend.…”
Section: Introduction 1| Backgroundmentioning
confidence: 99%